Highly Active under VIS Light M/TiO2 Photocatalysts Prepared by Single-Step Synthesis - Olga Thoda; Anastasia M. Moschovi; Konstantinos Miltiadis Sakkas; Ekaterini Polyzou; Iakovos Yakoumis (Applied Sciences, 2023)
A single-step impregnation approach is investigated as a synthetic route for photocatalyst synthesis active under visible light. The as-derived photocatalysts exhibited very high degradation rates towards methylene blue (MB) decolorization under visible light despite the high concentration of the initial MB solution concentration. The TiO2-based photocatalysts were prepared using nitrate precursor compounds for copper and silver; thus, Ag/TiO2 and Cu/TiO2 photocatalysts were prepared. The photocatalyst’s physicochemical properties were determined by XRF, BET, and XRD analysis. The metal nature of the titania substrate, the titania matrix effect, and the metal concentration parameters were studied, while the catalyst concentration in the MB initial solution was optimized.